2013
DOI: 10.4028/www.scientific.net/amr.844.314
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Polymer Composite: Low Natural Rubber, Cassava Starch and Palm Fiber

Abstract: The objective of this present work was to the preparation of polymer composite from low grade natural rubber (LNR), cassava starch (CSt) and palm fiber by using two-roll mill and then compression molding. The surface of palm fiber with different palm fiber lengths was analyzed by SEM. The tensile strength of the LNR/CSt composite containing 10% palm fiber with <425 µm fiber length was improved by addition of the 0.5 phr K2S2O8. After addition of K2S2O8, the swelling ratio in toluene of this composite was dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…The reduction was further supported by the increased hindrance exerted at higher filler loadings. The work of Riyajan and Riyapan (2013) reported that the % swelling ratio of starch/natural rubber composite decreased as the concentration of cassava starch moved from 10 phr to 40 phr filler loading. This behaviour applied to all the different starch-filled rubber under investigation.…”
Section: Naturalmentioning
confidence: 99%
“…The reduction was further supported by the increased hindrance exerted at higher filler loadings. The work of Riyajan and Riyapan (2013) reported that the % swelling ratio of starch/natural rubber composite decreased as the concentration of cassava starch moved from 10 phr to 40 phr filler loading. This behaviour applied to all the different starch-filled rubber under investigation.…”
Section: Naturalmentioning
confidence: 99%
“…The palm fiber's average elongation at break attains 30.88 ± 5.77% and the bamboo fiber's average elongation at break is 5.85 ± 0.15% (Chen et al 2017a,b). Due to their excellent mechanical properties, palm fibers are widely used as reinforcing materials in polymers, composites, and nanocomposites (Jacob 2004;Riyapan 2013;De Campos 2017). Figure 1 presents the digital micrographs of the palm tree and palm fibers.…”
Section: Introductionmentioning
confidence: 99%